Effectiveness of Ovitrap as a Control Tool Population Aedes Spp. In Areas Endemic to Dengue Fever Ternate City - Sumiati Tomia; UPIK KESUMAWATI HADI; yusuf, SUSI SOVIANA; Hartati, ELOK BUDI RETNANI (International Journal of Scientific Research and Management (IJSRM), 2023)
The mosquito ovitrap is often used in dengue fever (DF) vector surveillance, but it has never been reported in control programs to reduce the vector population. This study aims to determine the ovitrap effectiveness as a vector control instrument for DF. The research was carried out from January to March 2021 in Bastiong Talangame Village, one of the DF endemic villages, which is a densed settlement in Ternate City. This research was a quantitative pre-experimental design type one group pre-test and post-test . Measurement of the density of Aedes spp. larvae presented in the House Index (HI), Container Index (CI), and Breteau Index (BI) were carried out four times before and after ovitrap installation. The installation of ovitraps was carried out in 100 houses, where four ovitraps were installed in each house with an installation time of four weeks. The results showed that the ovitrap index value decreased until it reached the moderate category in the last week of observation. The density of larvae based on the calculation of HI, CI, BI showed a significant decrease (p = 0.0001) before and after ovitrap installation, with the density figure value of the high category being the medium category. The use of ovitrap was effective in reducing the population of Aedes spp. so it should be considered in the dengue vector control strategy